Normalizacja stosunków polsko-niemieckich – proces wciąż trwający? - Bielawska, Agnieszka (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
Polish-German relations are currently shaped by mutual understanding and collaboration. However, this does not prevent conflict of interests occurring between the two states with respect to foreign policy, or their standpoints, presented on the European arena. Nevertheless, these conflicts are a regular and permanent element of international relations, and the consequence of different geographical locations differences in the level and development directions of the economy of bcountries,d particularly of the primary responsibility of each state to act in the interest of its own citizens.